(untitled) (LEARNing Landscapes, 2023)
This article shares the story of a preschool teacher who courageously embarked on a yearlong journey of re-envisioning how an important milestone in children’s lives—their birthdays—were celebrated in the classroom. She accepted the preschool leadership’s invitation to align birthday practices with the center’s identity influenced by the Reggio Emilia Approach. What resulted was the teacher co-constructing a new set of rituals with the children that contributed to more equitable spaces that celebrated children’s individuality and fostered agency within an inclusive child-centered, children-driven learning environment.